Synchronisation of two separate zones in a standalone microgrid - Ying-Yi Hong; Chun-Yi Liu; Yung-Ruei Chang; Yih-Der Lee; Der-Chuan Ouyang (The Journal of Engineering, 2017)
Standalone microgrids that comprise distributed generation sources (DGSs) or energy storage systems (ESSs) exist on off-shore islands or remote areas. When a fault occurs in a standalone microgrid, the microgrid is separated into several zones with pre-specified DGS or ESS supplying power to local loads. After the fault is cleared, the three-phase voltages and frequencies may differ among these zones. To restore the original microgrid topology, these zones must be reconnected to each other by synchronisation. A synchronisation controller of the DGS/ESS that accounts for slightly different three-phase voltages and frequencies in two separate zones is presented. The Clark transform and Mamdani fuzzy rules are used to implement the controller, providing fast and seamless synchronisation. Simulation results using a standalone microgrid show the practical applicability of the proposed method.